Intra ocular pressure and central corneal thickness in hypertensive and non-hypertensive patients - Habib, Rehab; Javed, Muhammad Mohsin; IJAZ, FARHAT; Aftab, Khurram; Sohail, Hira; Aftab, Rana Rakhshan (Pakistan Journal of Physiology, 2020)
Background: Insulin resistance (IR) is a metabolic state characterized by progressive decline in insulin sensitivity. The aim of this study was to evaluate the association of the Body Mass Index and Waist-hip ratio with insulin resistance in non-alcoholic fatty liver disease patients. Methods: This cross-sectional study was conducted in King Edward Medical University Lahore during 2016–17. A total of 148 non-alcoholic fatty liver disease (NAFLD) subjects aged 40–60 years were enrolled by non-probability convenient technique. Fasting blood samples of each subject were drawn. Anthropometric measures were recorded. Fasting sugar levels were checked on glucometer and serum insulin levels were determined by sandwich ELISA technique. Homeostatic model assessment-insulin resistance (HOMA-IR) was calculated by recorded glucose and insulin levels. All participants were divided into insulin resistance and non-insulin resistance group on basis of cut-off points of HOMA-IR value 2.5. Results: Study was comprised of 148 subjects with fatty liver disease. Mean±SD of age, Body mass index and waist to hip ratio of the participants were 44.81±6.20, 31.25±4.26, 0.94±0.05 respectively. Of total subjects, 70.9% were female and 29.1% were male. Eighty-six (58.1%) of total subjects had insulin resistance and 62 (41.9%) were non-insulin resistance subjects. Significant positive association of insulin resistance was found with Body mass index (p=0.01). Insulin resistance was not associated with waist to hip ratio (p=0.35), or waist circumference (p=0.5). Conclusion: BMI has positive correlation on insulin resistance, while WHR is not related to insulin resistance. Pak J Physiol 2020;16(1):17–9